Pengaruh Motivasi Dan Sikap Terhadap Keputusan Pembelian Sepeda Motor Honda Vario 150cc (Studi Pada Pengguna Honda Vario 150cc) - Dahlia Dahlia; Intisari Haryanti (JURNAL EKUIVALENSI, 2021)
This study aims to determine and analyze the influence of motivation and attitudes on purchasing decisions for Honda Vario 150cc motorbikes (a study on Honda Vario 150cc users). This type of research is associative. The population used in the study were all users of Honda Vario 150cc motorbikes in Bima City whose numbers were unknown. The sample in this study were 96 respondents using the unknown population formula, the sampling technique used was purposive sampling. The data collection techniques used were observation, questionnaires and literature study. The data analysis technique used is validity test, reliability test, classical assumption test, multiple linear regression analysis, multiple correlation, determination test, t test and f test. Based on the results of the statistical analysis of the variable t test, it shows that motivation and attitudes have an effect on purchasing decisions for Honda Vario 150cc motorbikes (a study on Honda Vario 150cc users. Meanwhile, based on the results of the f test, it is known that motivation and attitudes have an effect on purchasing decisions for Honda Vario 150cc motorbikes. studies on Honda Vario 150cc users).